(untitled) (Herald of the National Children’s Medical Center, 2025)
Xyluria is a rare condition characterized by the presence of xylus (lymphatic fluid) in urine, in which urine becomes milk-like or fuzzy. Although parasitic infections are the most common cause of xyluria in endemic areas, non-parasitic or idiopathic conditions may also occur. This article shows the effective results of the laparoscopic approach using the example of a young patient with long-term idiopathic xyluria.